2022
DOI: 10.3390/w14223785
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Ecological Risk Assessment of Heavy Metals in the Sediment of a Tropical Mangrove Wetland on Hainan Island, China

Abstract: Mangroves have a high ecological service value and play an important role in achieving carbon neutrality. However, mangrove wetland soil quality is constantly being affected, and the ecological services provided are gradually declining due to the threat of various pollutants, especially heavy metal pollution. Exploring the sources and ecological risks of heavy metals in mangrove sediments will be helpful in improving mangrove protection. In 2020, sediments were collected from terrestrial and aquatic areas of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Dongzhai Harbor Mangrove Wetland is in Haikou City, Hainan Province, northeast of Hainan Island, with a tropical maritime monsoon climate. The average annual temperature is 17.1 • C, the average annual precipitation is 1676 mm, and the all-weather irregular tides have an average tidal range of approximately 1 m (Figure 1) [12]. Dongzhai Harbor is a drowned-valley-type harbor formed by the collapse of the 1605 Qiongshan earthquake, and is injected by small streams such as the Zhuxi River, Qiaotou River, and Yanfeng River.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Dongzhai Harbor Mangrove Wetland is in Haikou City, Hainan Province, northeast of Hainan Island, with a tropical maritime monsoon climate. The average annual temperature is 17.1 • C, the average annual precipitation is 1676 mm, and the all-weather irregular tides have an average tidal range of approximately 1 m (Figure 1) [12]. Dongzhai Harbor is a drowned-valley-type harbor formed by the collapse of the 1605 Qiongshan earthquake, and is injected by small streams such as the Zhuxi River, Qiaotou River, and Yanfeng River.…”
Section: Study Areamentioning
confidence: 99%
“…The environmental pressure on mangrove wetlands is increasing due to the increase in the population, the development of industrial and agricultural production in cities and watersheds, and especially the extensive selection of bay estuaries as sewage disposal sites for coastal cities, which has led to a large amount of pollutants entering the estuarine area [10,11]. In 2020, Mao et al [12], through the analysis of nine heavy metals in mangrove wetland sediments in Dongzhai Harbor, found that the content of heavy metals such as Cd, Cr, Cu, Ni, Zn, and Co in this area exceeded the standard, and the potential ecological risk and the quality of the concentration of the multiple possible impacts showed that the area with high concentrations of heavy metals and the surface of the sediment in the range of 0-20 cm were more susceptible to contamination by heavy metals. Studies have shown that the distribution of heavy metals in mangrove wetland sediments is closely related to changes in land-use patterns [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ma Yongling [21] collected the sediment digestion of Wuhe Wetland and determined 6 kinds of heavy metals (As, Cd, Cu, /b110>Hg, Pb, and Zn). The results show that the heavy metal content in the surface sediments of Wuhe wetland is mostly higher than that of the environmental background value, and the potential ecological risk assessment shows that the potential ecological hazard index in the sediments of Wuhe wetland is extremely strong ecological hazard.…”
Section: Research Progress Of Urban Wetland Sedimentmentioning
confidence: 99%